A rare case of 22-year-old male having spindle cell sarcoma and distant metastasis - Mehta, Moksha K.; Prajapati, Nisarg J.; Soni, Aanshi; Shah, Yena; Bhatt, Vraj D. (International Journal of Research in Medical Sciences, 2024)
Sarcomas are a group of cancers that have varied presentations in different locations in our bodies, can metastasize and show a range of histopathological features and are very uncommon. We report a case of a 22-year-old male presented with a case of high-grade spindle cell sarcoma in the posterior mediastinum of size 13×13×8 cm3 along with left moderate pleural effusion of the left lung. There are also multiple enhancing hypodense lesions in other parts of the body indicating neurofibromatosis. The tumor was detected using CECT Chest, Abdomen, an MRI was also done and results were confirmed by IHC. The patient was given chemotherapy however that only resulted in subsequent increase in size of the tumor since the patient did not report for the treatments regularly. This shows how important it is to be consistent with the treatment, failure of which results in grave consequences.